A227 ASSESSING THE BIOEQUIVALENCE OF NON-PRESCRIPTION ESOMEPRAZOLE 20 MG BANDED CAPSULES AND MULTIPLE-UNIT PELLET SYSTEM TABLETS UNDER FASTED AND FED CONDITION. (1st March 2018) - Kumaran, V; Li, J; Pollack, C; Moreira, S
Abstract: Background: Esomeprazole (ESO) 20 mg will soon be available in Canada without a prescription for treating frequent heartburn. Aims: This study assessed bioequivalence between ESO 20 mg multiunit pellet system (MUPS) tablets and banded capsules. Methods: This open-label, randomized, 6-period crossover, partial-replicate study administered single doses of each study drug to healthy males and females under fasted and fed conditions. Reference product (banded capsules) administration was replicated in both the fasted and fed states to establish intrasubject variability for determining the bioequivalence method that will be used. For endpoints with high variability (based on intrasubject standard deviation [SD]) with the reference product (Swr ≥0.294) a reference-scaled average bioequivalence (RSAB) approach was used; an unscaled approach was used for endpoints with low intrasubject variability (Swr <0.294). The primary endpoints were ESO area under the concentration-time curve from zero to infinity (AUCinf ) and peak plasma concentrations (Cmax ) while fasted and fed. Bioequivalence was based on the geometric mean ratios (GMRs) being within 0.80, 1.25 and 95% criteria bound (CB) being ≤0 for the RSAB approach, and the 90% confidence intervals (CIs) of the GMR being within 80%, 125% for the unscaled approach. Results: Of the 60 randomized subjects, 46 (76.7%) completed all study periods. While fasted, the mean (SD) ESO AUCinf was 1035.5 (925.7) ng*h/mL for the banded capsules and 985.5 (802.1) ng*h/mL for the MUPS tablets. The GMR (90% CI) was 0.948 (0.890, 1.010), indicating bioequivalence (unscaled). The fasted mean (SD) ESO Cmax was 511.3 (287.5) ng/mL for the banded capsule and 528.3 (292.1) ng/mL for the MUPS tablet. The GMR (95% CB) was 1.009 (-0.050), indicating bioequivalence (RSAB). Consistent with historical data, ESO AUCinf and Cmax were noticeably lower in the fed state for the ESO 20 mg banded capsule (537.9 [538.2] ng*h/mL; 154.5 [109.7] ng/mL) and MUPS tablet (637.1 [586.8] ng*h/mL; 217.9 [162.0] ng/mL) versus the fasted state. The GMR (95% CB) for AUCinf met bioequivalence criteria (0.994 [-0.061]), but Cmax (1.341 [-0.156]) did not (both RSAB). Conclusions: The ESO 20 mg MUPS tablets and banded capsules were found to be bioequivalent based on ESO AUCinf and Cmax under fasted conditions, suggesting these products can be used interchangeably. ClinicalTrials.gov Registration: Per the FDAAA 801 definition of an applicable clinical trial, this phase 1 trial was not registered. Funding Agencies: Medical writing support was provided by Dennis Stancavish of Peloton Advantage, LLC, and was funded by Pfizer Inc.